2010
DOI: 10.3390/v2040880
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 RT Inhibitors with a Novel Mechanism of Action: NNRTIs that Compete with the Nucleotide Substrate

Abstract: HIV-1 reverse transcriptase (RT) inhibitors currently used in antiretroviral therapy can be divided into two classes: (i) nucleoside analog RT inhibitors (NRTIs), which compete with natural nucleoside substrates and act as terminators of proviral DNA synthesis, and (ii) non-nucleoside RT inhibitors (NNRTIs), which bind to a hydrophobic pocket close to the RT active site. In spite of the efficiency of NRTIs and NNRTIs, the rapid emergence of multidrug-resistant mutations requires the development of new RT inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…Our discovery now establishes NcRTI as a novel class of RT inhibitors comprised of at least two chemical classes, the indolopyridones and benzofuranopyrimidone. It should be noted that a 4-dimethylamino-6-vinylpyrimidine (DAVP) series was proposed to belong to the NcRTI class (21,22). The DAVPs were shown to be competitive with dNTPs, yet representatives from this series show a Ͼ100-fold loss in potency against NNRTI-resistant mutants K103N and Y181I.…”
Section: Discussionmentioning
confidence: 99%
“…Our discovery now establishes NcRTI as a novel class of RT inhibitors comprised of at least two chemical classes, the indolopyridones and benzofuranopyrimidone. It should be noted that a 4-dimethylamino-6-vinylpyrimidine (DAVP) series was proposed to belong to the NcRTI class (21,22). The DAVPs were shown to be competitive with dNTPs, yet representatives from this series show a Ͼ100-fold loss in potency against NNRTI-resistant mutants K103N and Y181I.…”
Section: Discussionmentioning
confidence: 99%
“…These nanogel formulations have been successfully used in cancer chemotherapy as drug delivery systems for cytotoxic nucleoside analogues. 52,53 Another avenue that we are exploring is using nucleotide-competing RT inhibitors (NcRTIs) 54 instead of NRTIs in our bifunctional inhibitor designs, since NcRTIs are distinct from the chain-terminator NRTIs and do not require any phosphorylation by cellular kinases.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main focuses of past studies that targeted the inhibition of HIV-1 replication was reverse transcription, catalyzed by viral reverse transcriptase (RT) (13,29). Our initial data indicated that AH0109 acts at early stages of HIV-1 replication (Fig.…”
Section: Discussionmentioning
confidence: 99%